SKILLS MANAGEMENT SYSTEM AS A TOOL FOR STRATEGIC WORKFORCE PLANNING - Ardhianiswari Diah Ekawati (Bina Nusantara University, 2014)
Finding and retaining the right talent is an important issue for organizations worldwide. The definition of what is the right talent for the organization should be created first to make sure we recruit the right people and then the next question is what should be done after the right talent has been recruited? Skills Management Systems try to answer these questions by providing skills library and skills inventory for the organizations, thus the gap analysis between the available skills and ‘missing’ skills for the organization can be produced. This analysis accompanied with the prediction of skills demands in the future is a good base to develop a hiring policy and also development plans for the current employees. This paper describes the implementation of Skills Management System in a world-class research and development organization.